Hukum Tajam Ke Bawah Tumpul Ke Atas (Perspektif Sosiologis Penegakan Hukum di Indonesia) - Irwan Irwan; Fadjrin Wira Perdana; Doharman Lumban Tungkup; Miran Miran; Suteki Suteki (CV. Publikasi Indonesia, 2022)
Weak law enforcement and equitable development as well as other discriminatory treatments still occur in the implementation of minority rights in Indonesia. The purpose of this research is to examine law enforcement